Potential Test of Lactic Acid Bacteria from Infant Feces on The Growth of Staphylococcus epidermidis - Farras, Afif; Hasbi, Nurmi; Parwata, Wayan Sulaksmana Sandhi (Jurnal Biologi Tropis, 2024)
Staphylococcus epidermidis can cause various health infections such as in the urinary tract, respiratory tract, gastrointestinal tract, wounds, blood, and endocarditis. Treatment of S. epidermidis infections generally uses chemical antibiotics. However, the use of natural ingredients such as good bacteria such as Lactic Acid Bacteria (LAB) can be used as an alternative in treating infections by S. epidermidis. LAB is a probiotic that has benefits on human health. This study aims to determine the antibacterial potential of LAB against the growth of S. epidermidis. This research is a laboratory experimental research with post test only design. The stage starts from making media for test bacteria. Then the bacterial rejuvenation stage was carried out using the media that had been made. After the bacteria grow on the media, the bacteria are made into a suspension. Furthermore, antibacterial tests were carried out using the agar well diffusion method and each treatment was carried out as many as 3 repetitions. All isolates were found to be able to produce inhibition zones against S. epidermidis with 3 isolates with codes 01A 10-5, 01A 10-6 (2), and 03A 10-7 (1) categorized as moderate and 5 isolates with codes 01F 10-6 (2), 01F 10-7 (2), 02AF 10-7 (1), 03AF 10-7 (2), and 04AF 10-7 categorized as weak. The best zone of inhibition in the medium category was produced by locus-shaped LAB isolates. Based on the results of this study, it can be concluded that LAB from baby feces has antibacterial activity with weak to moderate strength, but the antibacterial activity is still classified as ineffective in inhibiting S. epidermidis. Further identification of antibacterial compounds in LAB from baby feces is recommended for quantitative analysis.